LONELINESS SEBAGAI FAKTOR RISIKO PSIKOPATOLOGI: STUDI LITERATUR - Ririn Dwiaryani S Pakaya; Nur Hikmah Alimudin; Nurafni Oktaviani Une; Dwi Naisha Ridwan; Eka Iriany Rahmania; Devy Sekar Ayu Ningrum (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Loneliness is a subjective experience arising from a discrepancy between desired and actual social relationships. This article aims to examine loneliness as a risk factor for psychopathology and its implications for clinical psychology practice. The study employed a narrative literature review method by analyzing literature from Google Scholar, PubMed, and Garuda using keywords related to loneliness, psychopathology, and mental health published between 2016–2026. The findings indicate that loneliness is associated with various mental disorders, including depression, anxiety, schizophrenia, personality disorders, and suicidal ideation. Loneliness contributes to psychopathology through cognitive, biological, and interpersonal mechanisms, such as social hypervigilance, negative cognitive distortions, and dysregulation of biological stress systems. Furthermore, loneliness and psychopathology demonstrate a reciprocal relationship that may worsen individuals’ psychological conditions. These findings highlight the importance of assessing and addressing loneliness in mental health services.